Using ontology for resume annotation. (1st January 2011) - Ben Abdessalem Karaa, Wahiba; Mhimdi, Nouha
Employers collect a large number of resumes from job portals or from their company's own website. These documents are used for an automated selection of candidates satisfying the requirements and therefore reducing recruitment costs. Various approaches for process documents have already been developed for recruitment. In this paper, we present an approach based on semantic annotation of resumes for an e-recruitment process. The most important task consists of modelling the semantic content of these documents using ontology. The ontology is built taking into account the most significant components of resumes inspired from the structure of EUROPASS CV. This ontology is thereafter used to annotate automatically the resumes.